Soviet Partisans in Lithuania in 1941–1944: Aspects of Repressive (Terrorist) Activity - Zizas, Rimantas (Genocidas ir rezistencija, 2010)
The article deals with the establishment of the Soviet armed underground in the years of the Nazi Germany occupation (1941–1944), revealing its complicated situation and reasons, predetermining its repressive activity aspects – the use of coercion and violence. The expression of those activity aspects, concrete attempts to effect terror acts (political assassinations) against the German occupational regime, Lithuanian administration officers, political and military figures are elucidated on the basis of archival sources. Soviet armed underground in Lithuania had the strong, many-sided and multiple repressive origin. In the spring of 1941–1942, the most important role in the organization of Soviet resistance belonged to the USSR NKGB–NKVD bodies. Already in July-August 1941, twelve NKGB–NKVD groups, 85 people, were sent to Lithuania for terrorist (also for intelligence and sabotage) actions. Those groups were not able to develop any activities in Lithuania, almost all participants of those groups perished. From the end of 1942, the Soviet partisan resistance was organized and guided by the Communist Party institutions, attempting to organize the Soviet underground on the broader political and social basis. The participants of the Soviet underground were: 1) groups sent from the Soviet rear; 2) Soviet prisoners of war; 3) Jews who avoided the holocaust; 4) Lithuanian (and of other countries) inhabitants of other nationalities, most of whom suffered the German repressions. On the eve of the war (1940), in the USSR-occupied and annexed Lithuania, no prerequisites and conditions existed for the Soviet underground activity, the majority of the population did not support it, its participants maintained their existence only by repressions, coercion and violence. Directives for terrorist actions were given from the leading centres in the Soviet rear. Soviet partisans prepared unsuccessfully actions against the high-rank German occupational regime officers (General Commissioner in Lithuania Adrian von Renteln, Vilnius Command Commissioner Horst Wulff, etc.), the organizer of the local Lithuanian detachment Gen. Povilas Plechavičius. On the initiative of the Lithuanian national underground and supported by its participants, the Soviet partisans in March 1944 in the Švenčionys County killed two German leading economic executives (Fritz Ohl and Ernest Heinemann). The article, on the basis of indirect sources, makes a presumption that special Soviet underground groups at the end of April 1944 near Kaunas murdered the high-rank Orthodox Church clergyman Sergyi (Voskresenski).